‘A workshop of the mind’: Aby Warburg, Fragmente zur Ausdruckskunde, edited by Ulrich Pfisterer and Christian Hönes. Berlin: Walter de Gruyter, 2015. Volume 4 of Aby Warburg: Gesammelte Schriften. - Matthew Rampley (Journal of Art Historiography, 2016)
This review considers the publication of the full text of Aby Warburg’s Fragments towards a Monistic Psychology of Art. The Fragments have often featured in accounts of Warburg’s work, but this is the first time that a definitive version of the text has been made available. On the one hand publication confirms that the Fragments are an important collection of materials that reveal his evolving thematic and methodological concerns. On the other, however, the Fragments should be recognised for what they are: a document highlighting Warburg’s inability to determine a comprehensive conceptual framework. They show the difficulty he experienced trying to articulate his interests, and they also show that during the 20 years that he wrote them, his thinking evolved remarkably little. Although the Fragments will undoubtedly expand knowledge of Warburg, they are not coherent theoretical or methodological set of observations, despite the impression that giving them a title might suggest.